UJI KANDUNGAN PROTEIN PADA MIE SAGU - Fratama, Rizky Fratama; Hetrik, Muhammad; Ramadhan, Akmal; Cahyuda, Nazamri; Aliwasa, Aliwasa (Jurnal Agroindustri Pangan, 2024)
Protein is one of the most important ingredients in food. Protein is a source of amino acids containing the elements C, H, O and N which have no fat or carbohydrates. Protein also functions to increase muscle mass, in addition to increasing muscle mass protein also functions as a building and regulating substance. The purpose of protein protein testing is to determine the protein content contained in sago noodles. Protein testing through oxidation, which is often done by the Kjeldahl method, is an important analytical technique for determining protein content in a sample. This process begins with the deconstruction stage, where the sample is heated with concentrated sulfuric acid. The next stage is distillation, where ammonia formed during deconstruction is captured in boric acid solution. The final stage is titration, where the ammonia solution is titrated with hydrochloric acid (HCl) to determine nitrogen levels. The results obtained from 2 test samples, namely sample 1 as much as 0.131% protein content and sample 2 obtained as much as 0.168% protein content. The conclusion of the results of this test is to determine the protein content contained in sago noodles marketed to consumers. With the results of this protein test provides information about the protein content contained in sago noodles.